What is the Minimum Volume of Sample to Find Small Microplastics: Laboratory Experiments and Sampling of Aveiro Lagoon and Vouga River, Portugal - Joana C. Prata (Water, 2020)
Small microplastics (<1 mm) comprise a great fraction of microplastics (<5 mm) found in the environment and are often overlooked due to the constrains of transporting and filtering large volumes of water in grab samplings. The objective of this work was to determine the minimum volume for reliable quantification of small microplastics in the environment. Different volumes (0.1, 0.25, 0.5, 1, 2.5 L) of laboratory spikes (fresh and saltwater) and environmental samples were filtered. Sampling volumes of 0.5 L or 1 L are a good compromise between drawbacks, such as effort, time, organic and mineral matter, potential contamination, and reliability of results, evaluated by interquartile range, accuracy, coefficient of variation, and recovery rates. Moreover, the observation of Nile Red-stained environmental samples under 470 nm produced six-times higher concentrations than samples under 254 nm, namely, 18 microplastics L−1 and 3 microplastics L−1 for the Aveiro Lagoon and 1 microplastics L−1 and 0 microplastics L−1 for the Vouga River, Portugal. This work also raises concerns about the underreporting of environmental concentrations of microplastics.